Approach to measurements at the nano level, with an emphasis on biomedicine - Ernesto José López González; Yolanda Cabrera Macías; Tatiana de las Mercedes Escoriza Martínez; Marle Pérez de Armas; Ernesto López Cabrera (Medisur)
This article aims to alert about the relevance of nanosciences and nanotechnology accompanied by nanometrology for the nations development in the 21st century. Scielo was used as a database, with the keywords: nanotechnology, nanomedicine, Cuban health units. The article makes an approach to nanotechnology with an international and regional approach. It describes some applications of nanotechnologies, with an emphasis on nanomedicine, as well as the dilemmas and ethical considerations associated with them. It advises about these developments’ harmfulness to human health, also defends the idea that nanometrology is essential for the technological developments achievement, with greater relevance in the nanomedicine field, as well as that nanotechnology should be treated as the 21st century science due to the social, cultural and economic impact that will have, and this can change the world.